CP-045 Over level progression free survival of azacitidine in myelodysplastic syndrome and in acute myeloid leukaemia. (25th February 2017) - Cascone, V; Distefano, G; Zampogna, L; Poidomani, M; Antolino, A; Garozzo, G; Rizza, G; Drago, G
Abstract : Background: Azacitidine belongs to the group of antimetabolites (an analogue of cytidine) used in myelodysplastic syndrome (MS) and in acute myeloid leukaemia (AML), with expected progression free survival(according to the characteristics product summary) of 24.6 months for patient with MS and AML with blasts ≤30%. Purpose: To describe the clinical cases of patients affected by MS and AML. Material and methods: We performed a retrospective study enrolling all patients with MS and AML treated in our hospital. We looked at the medical records and AIFA monitoring folders, and compared effectiveness with progression free survival in the characteristics product summary. Results: 21 patients were treated with azacitidine: 9 patients were affected by ALM and 12 patients were affected by MS. In the first group, we had 8 responders and 1 non-responder (treatment outcome determined with follow-up at 6 months); in the second group there were 4 non-responders. According to clinical studies with a protocol of azacitidine 1–6 +1, the administration method used was: intramuscularly for 6 days (Monday–Saturday) with a break on Sunday and the last administration on the following Monday, repeated every 28 days. We observed a longer progression free survival in two patients. The patient affected by MS, 68 years old, had white blood cells 1600, haemoglobin 8.4 and platelets 25 000 at the start of treatment. He was classified as intermediate–high risk with blasts 5–10%. The patient was treated with azacitidine for 60 months, with an increase in progression free survival of 35.4 months. The patient dropped out of therapy for progression; he is alive and is doing supportive care. The patient affected by ALM, 76 years old, had white blood cells 30 400, haemoglobin 7.9 and platelets 41 000 at the start of treatment. Blasts were >20%. The patient was treated with azacitidine for 59 months, with an increase in progression free survival of 34.4 months. He is still being treated with azacitidine. Conclusion: We have shown a high efficacy for azacitidine in increasing the progression free survival in most patients treated, with two over level clinical cases (10% of the patients studied). No conflict of interest